2021
DOI: 10.1039/d0fo03377d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of psyllium seed husk powder, methylcellulose, pregelatinised starch, and cold water swelling starch on the production of gluten free crackers

Abstract: The production of gluten free crackers is challenging because the formation of a gluten network is required. This study investigated the effects of psyllium seed husk powder (PSY), methylcellulose (MC),...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…As for cracker hardness, the crackers produced using the separated-dough method all had lower hardness than PSY and PGS crackers (hardness of 801 g and 667 g respectively) prepared without the separated-dough method as reported in our separ-ated study. 6 As for the influence of the mixing time, although the influence was insignificant, a tendency can be observed that hardness increased but fracturability decreased with the increase in mixing time which was associated with a reduction in structural heterogeneity. Because long mixing time led to a reduction in the heterogeneity of structure and water distribution while short mixing time might lead to handling problems and weak structure due to high heterogeneity, an intermediate mixing time, 60 s, was chosen for the following studies.…”
Section: Papermentioning
confidence: 94%
See 4 more Smart Citations
“…As for cracker hardness, the crackers produced using the separated-dough method all had lower hardness than PSY and PGS crackers (hardness of 801 g and 667 g respectively) prepared without the separated-dough method as reported in our separ-ated study. 6 As for the influence of the mixing time, although the influence was insignificant, a tendency can be observed that hardness increased but fracturability decreased with the increase in mixing time which was associated with a reduction in structural heterogeneity. Because long mixing time led to a reduction in the heterogeneity of structure and water distribution while short mixing time might lead to handling problems and weak structure due to high heterogeneity, an intermediate mixing time, 60 s, was chosen for the following studies.…”
Section: Papermentioning
confidence: 94%
“…The dough samples were prepared and sheeted as described in section 2.3. Wheat cracker dough was also prepared as described in a separate study by our research group 6 and measured as a positive control. The dough sheet was cut with Food & Function Paper a circular cutter (50 mm in diameter) and transferred onto the rheometer.…”
Section: Dough Expansionmentioning
confidence: 99%
See 3 more Smart Citations